Lords of the Horizons : A History of the Ottoman Empire - Goodwin, Jason (London Vintage Books, 1999)
The Ottoman Empire has long exerted a strong pull on Western minds and hearts. For over six hundred years the Empire swelled and declined; rising from a dusty fiefdom in the foothills of Anatolia to a power which ruled over the Danube and the Euphrates with the richest court in Europe. But its decline was prodigious, protracted, and total.
Include An Ottoman Chronology,Glossary,Bibliography and Index.
Keywords: Ottoman Empire. -- Turkey -- History -- Ottoman Empire, 1288-1918. -- Turkey